A novel aryl-guanidinium derivative, VP79s, targets the signal transducer and activator of transcription 3 signaling pathway, downregulates myeloid cell leukaemia-1 and exhibits preclinical activity against multiple myeloma - Mc Elligott, Tony; Rozas, Isabel; Zisterer, Daniela; Hayden, Patrick; Lynam-Lennon, Niamh; Browne, Paul (My University, 2022)
Aims: We have recently described a novel guanidinium-based compound, VP79s, which induces cytotoxicity in various cancer cell lines. Here, we aim to investigate the activity of VP79s and associated mechanisms of action in multiple myeloma (MM) cells in vitro and ex vivo. Main methods: The effects of VP79s on cell viability and induction of apoptosis was examined in a panel of drug-sensitive and drug-resistant MM cell lines, as well as ex vivo patient samples and normal donor lymphocytes and platelets. Cell signaling pathways associated with the biological effects of VP79s were analysed by immunoblotting and flow cytometry. Gene expression changes were assessed by quantitative real-time PCR analysis. Key findings: VP79s was found to rapidly inhibit both constitutively active and IL-6-induced STAT3 signaling with concurrent downregulation of the IL-6 receptors, CD130 and CD126. VP79s induced a rapid and dose-dependent downregulation of anti-apoptotic Bcl-2 family member, myeloid cell leukaemia-1 (MCL-1). VP79s enhanced bortezomib induced cell death and was also found to overcome bone marrow stromal cell induced drug resistance. VP79s exhibited activity in ex vivo patient samples at concentrations which had no effect on peripheral blood mononuclear cells, lymphocytes and platelets isolated from healthy donors. Significance: As VP79s resulted in rapid inhibition of the key IL-6/STAT3 signaling pathway and downregulation of MCL-1 expression with subsequent selective anti-myeloma activity, VP79s may be a potential therapeutic agent with a novel mechanism of action in MM cells.
PUBLISHED
Keywords: Anti-cancer therapeutics; Drug discovery; MCL-1; Multiple myeloma; STAT3; Signal transducer and activator of transcription 3; Cancer; APOPTOSIS; Apoptosis; Apoptosis; Apoptosis; Apoptosis and cancer; Apoptosis, molecular control; Biology and therapy of myeloma; Blood Cancers; CELL APOPTOSIS; CELL SIGNALING; CHEMOTHERAPY-INDUCED APOPTOSIS; Cancer drug discovery; Cellular and molecular mechanisms regulating and resisting apoptosis; DRUG DISCOVERY; Drug Discovery; Drug discovery; Drug discovery, profiling, targeting; INDUCE APOPTOSIS; INDUCED APOPTOSIS; MULTIPLE MYELOMA; MULTIPLE-MYELOMA; MYELOMA; Molecular mechanisms underlying apoptosis & cell cycle; Multidisciplinary approach to drug discovery and development; Multiple Myeloma; pre-clinical assessment